Methods for reducing buyer perceived risk related to the adoption of technological innovations. (1st January 2014) - Patala, Samuli; Jalkala, Anne; Soukka, Risto
Industrial technology suppliers marketing and selling technological innovations need to be able to reduce buyer perceived risk. Innovation buyers face high perceived risks, especially in the initiation and implementation phases of innovation adoption. We deliver insights on risk reduction tools by examining the case of a monitoring system innovation designed to enhance process efficiency in an electrolytic copper refining process. We examine the case from both the buyer and seller perspective and propose concrete methods that sellers can employ to reduce buyer perceived risk. At the initiation phase, we illustrate a life cycle-based tool for performance assessment. In the implementation phase, we identify three key supplier processes namely adaptation, championing, and cooperative implementation that may facilitate the buying firm's successful implementation of the innovation. The findings provide more in-depth understanding about the role of risk reduction in the marketing and procurement of technological innovations.